Brominated Depsidones with Antibacterial Effects from a Deep-Sea-Derived Fungus Spiromastix sp - Huang, Zequan; Liu, Dong; Chen, Shang; Ren, Jinwei; Gao, Chenghai; Li, Zhiyong; Fan, Aili; Lin, Wenhan (Marine drugs, 2024)
Eleven new brominated depsidones, namely spiromastixones U-Z5 (1–11) along with five known analogues (12–16), were isolated from a deep-sea-derived fungus Spiromastix sp. through the addition of sodium bromide during fermentation. Their structures were elucidated by extensive analysis of the spectroscopic data including high-resolution MS and 1D and 2D NMR data. Compounds 6–10 and 16 exhibited significant inhibition against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecium (VRE) with MIC values ranging from 0.5 to 2.0 μM. Particularly, tribrominated 7 displayed the strongest activity against MRSA and VRE with a MIC of 0.5 and 1.0 μM, respectively, suggesting its potential for further development as a new antibacterial agent.